TRAINING AND ASSISTANCE OF A LIVING PHARMACEUTICAL CULTURE BY UTILIZING A HOME YARD IN GAMPONG KARANG ANYAR, LANGSA BARO DISTRICT LANGSA CITY - Meutia Dewi; Suri Amilia; Muhammad Muaz Munauwar (LPPM dan PM Universitas Samudra, 2022)
Community service activities carried out at Karang Anyar Village, Langsa Baro District, Langsa City aimed to: (1) Socialize the types of traditional medicinal plants that are useful for health to housewives, (2) motivate the use of the yard for medicinal plants. traditional medicines, (3) using used materials as a medium for planting traditional medicines. This activity is carried out using counseling, discussion and question and answer methods. The training was carried out on how to plant and nursery by utilizing used goods as media. The result achieved in this activity is that the activity runs smoothly and in accordance with the previously determined plan because it gets positive appreciation from the village apparatus and the surrounding community, this can be seen from the licensing process to the final implementation of the activity. The community, especially housewives, were very enthusiastic in participating in this training activity because they wanted to become an independent and healthy community.